2018
DOI: 10.1111/gcb.14302
|View full text |Cite
|
Sign up to set email alerts
|

Satellite sun‐induced chlorophyll fluorescence detects early response of winter wheat to heat stress in the Indian Indo‐Gangetic Plains

Abstract: Extremely high temperatures represent one of the most severe abiotic stresses limiting crop productivity. However, understanding crop responses to heat stress is still limited considering the increases in both the frequency and severity of heat wave events under climate change. This limited understanding is partly due to the lack of studies or tools for the timely and accurate monitoring of crop responses to extreme heat over broad spatial scales. In this work, we use novel spaceborne data of sun-induced chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
68
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 178 publications
(83 citation statements)
references
References 90 publications
6
68
0
1
Order By: Relevance
“…The effects of vegetation structural variables were eliminated, then important information on drought events could be provided by SIF yield . Changes on vegetation greenness and chlorophyll content may not rapidly reflect the information about vegetation status under drought, but variations on the production of fluorescence have rapid responses to water stress [26,29,30,58]. Therefore, SIF yield is the suitable factor to detect the changes of vegetation function during the drought period in the study areas.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The effects of vegetation structural variables were eliminated, then important information on drought events could be provided by SIF yield . Changes on vegetation greenness and chlorophyll content may not rapidly reflect the information about vegetation status under drought, but variations on the production of fluorescence have rapid responses to water stress [26,29,30,58]. Therefore, SIF yield is the suitable factor to detect the changes of vegetation function during the drought period in the study areas.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Decreased penetration of sunlight for the crop has already spurred demand for breeding for high photosynthetic or radiation-use efficiency (Joshi et al 2007). These observations also suggest that sun-induced fluorescence could be a good direct proxy for the crop yield, as it carries information on light conditions, and was previously shown to perform better than VIs for yield estimation (Song et al 2018). Although NIRv was found superior to other VIs for estimating GPP (Badgley et al 2017), we did not detect any benefit of using it for the yield estimation.…”
Section: Impact Of Environmental Conditions On the Crop Yield As Captmentioning
confidence: 97%
“…Comparison of performances among models with one or two input variables, as well as the RAM analysis, showed that high yields in 2012 were associated with low temperatures accompanied by sunny conditions during the growing period, though most recent studies focus primarily on the impact of increasing temperatures in the Indian Wheat Belt (e.g. Duncan et al 2014, Jain et al 2017, Song et al 2018 and in other regions (Lobell et al 2005). As an important driver of photosynthesis, SW down affects the resources that crops can build during the growing season, which is apparently not fully reflected in the VIs.…”
Section: Impact Of Environmental Conditions On the Crop Yield As Captmentioning
confidence: 99%
“…Although it has been proven and well documented that oak powdery mildew has negative effects on the photosynthesis and transpiration of leaves (Hajji et al, 2009;Pap et al, 2014;Copolovici et al, 2014), there is a further need for better understanding the effects of this obligate leaf parasite on the photosynthetic apparatus, due to its complexity. For that purpose, chlorophyll a fluorescence measurement can provide useful additional information for understanding the primary events of photosynthesis and the effects of stress on photochemistry (Razavi et al, 2008;Ajigboye et al, 2016;Guo et al, 2016;Song et al, 2018). The main objective of this study was to access the impact of E. alphitoides on the leaf physiology, using non-destructive fluorescence parameters in combination with parameters of leaf gas exchange.…”
mentioning
confidence: 99%